Music in services marketing: an investigation about the roles music plays in service environments - Furtado, Wilderson Moisés (2018)
As a significant distribution of ambient music and the emergence of companies offering the environmental-musicalization service could be noted, this thesis aimed at investigating the roles of music in service environments. Herein, it was presented the evolution and application of music in marketing and services marketing researches in order to contextualize the state of art of the literature, such that the functionalities of music could afterwards be identified and categorized into roles. Moreover, the study discussed the market practices related to the utilization of music in service places and had these practices compared to the literature. It is important to mention that in this thesis, the service environments were found to be the restaurants and clothing stores, once the participants of the study brought cases and examples related to these contexts. Also, it is relevant to say that the thesis was conducted from the qualitative methodological approach and its design was based on the content analysis analytical approach. By this, a systematic review of the literature was conducted in the way the selection of music-in-marketing scholars followed some criteria and the thesis\' analytical goal of operationalizing the functionalities of music in service places could be justified. The field phase of the thesis\' content analysis was characterized by the in-depth interviews with marketing specialists that had been being dealing with the environmental music in service places and the operational observations in some musicalization providers and clients. Hence, three main roles could be identified to categorize the functionalities of music brought by the interviews and observations: the role of being a commodity, the role of being a sound, and the role of being inspirational. As a theoretical implication, it can be highlighted the influence of music on the service environment\' employees and vice-versa. As a practical implication, it was suggested to the musicalization providers and clients to target the consumer outcomes other than the stay duration.